2004
DOI: 10.1210/me.2003-0278
|View full text |Cite
|
Sign up to set email alerts
|

Antiestrogens Induce Growth Inhibition by Sequential Activation of p38 Mitogen-Activated Protein Kinase and Transforming Growth Factor-β Pathways in Human Breast Cancer Cells

Abstract: Antiestrogens are successfully used in the treatment of breast cancer. The purpose of this study was to investigate the role of different signal transduction pathways in antiestrogen-induced growth inhibition to gain insights into mechanisms of antiestrogen resistance. We used specific MAPK inhibitors and MCF-7 carcinoma cells as a model to demonstrate that p38 MAPK is an important mediator of antiestrogen growth inhibition in breast cancer. A kinase assay showed that antiestrogens (4-hydroxytamoxifen and ICI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 53 publications
(68 reference statements)
5
36
0
2
Order By: Relevance
“…22,23 In line with previous reports, fulvestrant effectively inhibited proliferation of ER-positive breast cancer cells. 37,38 Moreover, fulvestrant reduced the migratory activity of ER-positive MCF-7 cells, thus confirming previously reported results. 33 Importantly, we observed that fulvestrant also induced a significant upregulation of KAI1 in ERpositive but not ER-negative breast cancer cells in vitro.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…22,23 In line with previous reports, fulvestrant effectively inhibited proliferation of ER-positive breast cancer cells. 37,38 Moreover, fulvestrant reduced the migratory activity of ER-positive MCF-7 cells, thus confirming previously reported results. 33 Importantly, we observed that fulvestrant also induced a significant upregulation of KAI1 in ERpositive but not ER-negative breast cancer cells in vitro.…”
Section: Discussionsupporting
confidence: 84%
“…5a-d). 37,38 Fulvestrant also affected the migration of ER-positive MCF-7 breast cancer cells, thus confirming previously reported results (Fig. 5e).…”
Section: Kai1 Is a Target Of Er-mediated Gene Repressionsupporting
confidence: 90%
“…We additionally confirmed this putative crosstalk with a vice versa approach using a model system of ER-negative cancer cells, transfected to transiently overexpress the ER isoform ERa or ERb. These transfected MDA-MB-435 cells were completely sensitive to agonist and antagonist treatment and maximal effects on ligand-dependent receptor activation or inactivation were achieved in concentration ranges similar to those determined in prior stimulation experiments using ER-positive MCF-7 breast cancer cells [13,26]. Interestingly, these concentrations (10 -11 M E2, 10 -9 M ICI) also maximized the effects on growth induction or growth inhibition of untransfected MCF-7 cells [27,28].…”
Section: Discussionsupporting
confidence: 55%
“…Previous studies of our group emphasized the crucial role of TGF-b signaling in antiestrogen therapy and in the progression of breast cancer in general [6,[10][11][12][13]. By KaplanMeier analysis, we identified a correlation between the expression of TGF-b receptor II and a highly reduced overall survival in ER-negative breast cancer patients [14].…”
Section: Introductionmentioning
confidence: 79%
“…The authors acknowledge that those experiments confirm previously published observations by other research groups. [4][5][6][7] It seems that Christgen et al's only original and novel contribution is the finding that KAI1 is upregulated by fulvestrant in 2 ER-positive breast cancer cell lines.…”
mentioning
confidence: 99%